Elimination of Elaidic Acid and Enrichment of Omega-3 Fatty Acid in Industrial By-Product of Fish Processing - Maulana, Indra Topik; Sukrasno, Sukrasno; Damayanti, Sophi (Universitas Jenderal Soedirman, 2025)
ABSTRACT.